Experiences of case management with chronic illnesses: a qualitative systematic review. (15th January 2018) - Joo, J.Y.; Liu, M.F.
Abstract : Aim: This qualitative systematic review aimed to identify and synthesize recent qualitative studies to improve understanding of the experiences and perceptions of case management interventions that individuals with chronic illnesses and their caregivers have. Background/Introduction: Case management has been shown to be effective at improving quality of care and lowering costs for individuals with chronic illnesses. However, no qualitative review has been synthesized with recent qualitative studies about case management experiences by individual with chronic illnesses. Methods: This qualitative systematic review uses a thematic synthesis method to review 10 qualitative studies published within the last 10 years, from 2007 to 2016, thereby identifying and discussing the understandings that individuals with chronic illnesses and their caregivers have about case management. Results: From this synthesis, three themes were identified as facilitators of case management (access to healthcare resources, health status supports and emotional aid) and two themes were identified as barriers to it (low information about case management and time constraints). Conclusions: This is the first qualitative systematic review of the perceptions and experiences that individuals with chronic illnesses and their caregivers have about case management. The facilitators of case management can be employed to inform patients about the benefits of case management and to improve population health. Implications for nursing and health policy: The findings about barriers to case management can be used to reform case management for populations with chronic illnesses. These factors should be considered by nursing researchers and healthcare policymakers when implementing case management.